Systematic Analysis of Donor and Isolation Factor’s Impact on Human Islet Yield and Size Distribution - Wang, Y (2013)
Islet transplantation is a promising therapy for type I diabetes mellitus, with both islet yield and islet size playing important roles in transplant outcomes. Some key factors influencing islet yield have been identified, but with conflicting results. In this study, we analyzed 276 islet isolations performed at a single center to identify variables that influence islet yield, and additionally, influence islet size and size distribution. Pearson correlation analyses demonstrated that donor BMI had a positive correlation with pancreas size, actual islet count (AIC), and islet equivalent (IEq)/g (all p ≤ 0.009), while CIT had a negative correlation with AIC and IEq/g (all p ≤ 0.003). However, neither BMI nor CIT had any correlation with islet size or islet size distribution. Donor age, sex, and organ preservation solutions were shown to have no correlation with islet yields and size distribution. Finding a balance between digestion time and digestion rate is important for islet yield and size distribution this is demonstrated when an isolation is overdigested (median split: >74%) there is an increase in islet counts, however there is also an increase in smaller islets produced. Of the three collagenases analyzed, Sigma V had the lowest digestion rate, (mean=65%), approximately 5% and 10% lower than Roche Liberase HI (p = 0.04) and Serva NB1(p = 0.0003), respectively; however the Sigma V group showed better islet size preservation than the other two enzymes. Yet, overall the enzymes resulted in similar IEq/g digested tissue. Among 276 isolations, 70.2% of the isolated islets were smaller than 150 μm, the average in situ size, and contributed only 20.4% to total IEq, while 7.4% of islets were larger than 250 μm, but contributed 42.4% to total IEq. In summary, BMI and CIT are the most useful donor variables for predicting islet yield, but selection of enzyme and balancing digestion time and digestion rate are also important for isolation success.